Daya Saing Teh Hitam Ekspor Indonesia di Perdagangan Internasional - Elpawati Elpawati; Bahagio Utama (Sharia Agribusiness Journal, 2021)
Black tea is one of the preparations of the tea plant that comes from the fermentation of tea leaves and is one of the leading commodities in the Indonesian plantation sub-sector, however Indonesian black tea has experienced a decline in export value in the last 10 years. The purpose of this research is to analyze the structure of the world black tea market, the comparative and competitive advantages of Indonesian black tea in the world market and the position of Indonesia's trade in black tea commodities in the world in the 2010-2019 period. The analytical tools used are the Herfindahl Hirschman Index (HHI), Concentration Ratio (CR), Revealed Comparative Advantage (RCA), Trade Specialization Index (TSI) and Export Dynamic Product (EPD). The comparison countries are Kenya, Sri Lanka, India and China, while the export destinations for black tea are Malaysia, Russia, Pakistan, Germany and the United States. The results of this study are (1) The structure of the world black tea market is a moderate oligopoly (2) Indonesia has the comparative advantage of black tea in the export destination country. (3) Indonesia’s black tea does not have a competitive advantage in the export destination country. (4) Indonesia's trade position in black tea commodity as an exporting country.Keywords: Black Tea, Market Structure, Comparative Advantage, Competitive Advantage, Trading Position.AbstrakTeh hitam merupakan salah satu olahan dari tanaman teh yang berasal dari fermentasi daun teh serta menjadi salah satu komoditas unggulan subsektor perkebunan Indonesia, tetapi teh hitam Indonesia mengalami penurunan nilai ekspor dalam 10 tahun terakhir. Tujuan dari penelitian adalah menganalisis struktur pasar teh hitam dunia, keunggulan komparatif dan kompetitif teh hitam Indonesia di pasar dunia dan posisi perdagangan Indonesia pada komoditas teh hitam di dunia dalam periode 2010-2019. Alat analisis yang digunakan adalah Herfindahl Hirschman Index (HHI), Concentration Ratio (CR), Revealed Comparative Advantadge (RCA), Trade Specialization Index (TSI) dan Export Dynamic Product (EPD). Negara pembandingnya adalah Kenya, Sri Lanka, India dan Cina, sedangkan negara tujuan ekspor teh hitam adalah Malaysia, Rusia, Pakistan, Jerman dan Amerika Serikat. Hasil dari penelitian ini adalah (1) Struktur pasar teh hitam dunia adalah oligopoli moderat. (2) Indonesia memiliki keunggulan komparatif teh hitam di negara tujuan ekspor. (3) Teh hitam Indonesia tidak memiliki keunggulan kompetitif di negara tujuan ekspor. (4) Posisi Perdagangan Indonesia pada komoditas teh hitam sebagai negara eksportir.Kata Kunci: Teh Hitam, Struktur Pasar, Keunggulan Komparatif, Keunggulan Kompetitif, Posisi Perdagangan.